2018
DOI: 10.1111/jsr.12674
|View full text |Cite
|
Sign up to set email alerts
|

Complement system activation in obstructive sleep apnea

Abstract: The complement system may play a role in the systemic inflammation characterising obstructive sleep apnea; however, this has not been investigated before. We aimed to study the involvement of effector complement elements in obstructive sleep apnea, namely C3a, C5a and SC5b-9. Venous blood was collected in 50 patients with obstructive sleep apnea and 26 control subjects in the evening and the following morning. Plasma complement proteins were analysed with ELISA. Complement factor levels were compared between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 29 publications
4
23
1
1
Order By: Relevance
“…Inpatient polysomnography and cardiorespiratory polygraphy were performed as described previously [2][3][4] using Somnoscreen Plus Tele PSG (Somnomedics GMBH Germany). Sleep stages, movements and cardiopulmonary events were scored manually according to the American Academy of Sleep Medicine [24] guidelines.…”
Section: Sleep Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Inpatient polysomnography and cardiorespiratory polygraphy were performed as described previously [2][3][4] using Somnoscreen Plus Tele PSG (Somnomedics GMBH Germany). Sleep stages, movements and cardiopulmonary events were scored manually according to the American Academy of Sleep Medicine [24] guidelines.…”
Section: Sleep Studiesmentioning
confidence: 99%
“…Chronic intermittent hypoxia and increased sympathetic tone induce production of pro-inflammatory molecules, such as interleukin (IL)-6, IL-1β, tumour necrosis factor-α [1] or complement elements [2] and suppresses the release of anti-inflammatory [3,4] molecules. Linked to inflammation and sympathetic activity, OSA is characterised by a hypercoagulation state [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Using a mouse model devoid of C5 complement signaling, rhythmic HPSC recruitment could be entirely blocked, implicating the importance of circadian complement pathway activation in immune surveillance (Massberg et al, 2007;Janowska-Wieczorek et al, 2012;Ratajczak et al, 2012;Budkowska et al, 2018). While this study implicates rhythmic complement activation in the context of circulating HPSCs, other studies have shown a sleep-dependent increases in C3, C4, C3a, C5a, and complement factor I (CFI) ultimately resulting in dysregulated cytokines production (Reis et al, 2011;Manzar et al, 2016;Horvath et al, 2018;Wadhwa et al, 2019). Using the Pittsburgh Sleep Quality Index (PSQI) in a relatively small number of male university students, Manzar et al demonstrated that poor sleep quality correlates with decreased proinflammatory C3 and C4 in the serum and increased levels of anti-inflammatory CFI during early bedtime and daytime (Manzar et al, 2015), suggesting that regular sleep patterns may be important for the normal cycling of complement factors.…”
Section: Co-regulatory Roles Of Complement and Sleep On Immunosurveilmentioning
confidence: 72%
“…Using the Pittsburgh Sleep Quality Index (PSQI) in a relatively small number of male university students, Manzar et al demonstrated that poor sleep quality correlates with decreased proinflammatory C3 and C4 in the serum and increased levels of anti-inflammatory CFI during early bedtime and daytime (Manzar et al, 2015), suggesting that regular sleep patterns may be important for the normal cycling of complement factors. Supporting this link, increased serum C3a levels in both evening and daytime was correlated with severity of obstructive sleep apnea (Horvath et al, 2018). Under optimal physiological conditions, complement regulatory factors including CR1, membrane cofactor protein (MCP; also known as CD46), and Factor H control the complement activation at the levels of C3 convertase and inhibit the formation of C5-C9 MAC that could be detrimental to host cells.…”
Section: Co-regulatory Roles Of Complement and Sleep On Immunosurveilmentioning
confidence: 93%
“…Full-night cardiorespiratory polygraphy and polysomnography were performed using the Somnoscreen Plus Tele PSG (Somnomedics GmbH Germany) as described previously 49 . Sleep stages, movements and cardiopulmonary events were scored manually according to the American Academy of Sleep Medicine (AASM) guideline 50 .…”
Section: Methodsmentioning
confidence: 99%